The 'Fifth Veda' of Hinduism : poetry, philosophy and devotion in the Bhāgavata Purāṇa /: poetry, philosophy and devotion in the Bhāgavata Purāṇa. (2016) - Theodor, Ithamar, 1959-
No abstract available